Artificial Intelligence and DNA in criminal investigations - Zenati, Mohammed Said (Naif Arab University for Security Sciences, 2025)
Artificial Intelligence is increasingly integrated into forensic science, revolutionizing the use of DNA evidence in criminal investigations. AI-driven tools, including machine learning algorithms, enable forensic experts to analyse complex DNA samples more accurately and efficiently than traditional methods. These tools facilitate the interpretation of low-level, degraded, or mixed DNA samples, which often challenge manual analysis. AI techniques such as probabilistic genotyping use advanced algorithms to assess the likelihood that DNA mixtures contain material from specific individuals, improving identification accuracy in cases with multiple contributors. The adoption of AI in DNA analysis enhances investigative capabilities by automating the processing of large and complex datasets, allowing law enforcement to extract critical genetic information quickly. AI also supports the resolution of cold cases by making it possible to analyse decades-old or difficult samples that were previously unviable for testing. Experts emphasize that AI does not replace forensic scientists but serves as an advanced aid that increases the sensitivity and specificity of DNA interpretation while reducing human bias and errors. Alongside technical benefits, the use of AI in forensic DNA analysis brings procedural and legal challenges, especially regarding the transparency and validation of AI algorithms. Courts must ensure the reliability of AI-based evidence and demand clear documentation of the algorithms’ validation processes, reproducibility, and error rates. Legal scrutiny focuses on addressing issues related to "opaque AI" systems, where the decision-making process is not always transparent, raising concerns about admissibility and interpretability in court. Overall, the integration of AI in forensic DNA analysis marks a significant advancement in criminal justice by enhancing the accuracy and efficiency of investigations. The technology's continued development, alongside the establishment of rigorous validation protocols and ethical considerations, is critical for its successful implementation in forensic science and the criminal justice system الملخص: يتم دمج الذكاء الاصطناعي بشكل متزايد في علم الطب الشرعي، مما أحدث ثورة في استخدام أدلة الحمض النووي في التحقيقات الجنائية. تتيح الأدوات التي تعتمد على الذكاء الاصطناعي، بما في ذلك خوارزميات التعلم الآلي، للخبراء الجنائيين تحليل عينات الحمض النووي المعقدة بشكل أكثر دقة وكفاءة من الطرق التقليدية. تسهل هذه الأدوات تفسير عينات الحمض النووي منخفضة المستوى أو المتدهورة أو المختلطة، والتي غالبًا ما تشكل تحديًا للتحليل اليدوي. تستخدم تقنيات الذكاء الاصطناعي، مثل التنميط الجيني الاحتمالي، خوارزميات متقدمة لتقييم احتمالية احتواء خليط الحمض النووي على مواد من أفراد معينين، مما يحسن دقة تحديد الهوية في الحالات التي يوجد فيها عدة مساهمين. يعزز استخدام الذكاء الاصطناعي في تحليل الحمض النووي قدرات التحقيق من خلال أتمتة معالجة مجموعات البيانات الكبيرة والمعقدة، مما يسمح لسلطات إنفاذ القانون باستخراج المعلومات الجينية الهامة بسرعة. كما يدعم الذكاء الاصطناعي حل القضايا المعلقة من خلال إتاحة تحليل عينات قديمة أو صعبة كان من المستحيل اختبارها في السابق. ويؤكد الخبراء أن الذكاء الاصطناعي لا يحل محل علماء الطب الشرعي، بل يعمل كأداة مساعدة متطورة تزيد من حساسية وخصوصية تفسير الحمض النووي مع تقليل التحيز البشري والأخطاء. إلى جانب الفوائد التقنية، يطرح استخدام الذكاء الاصطناعي في تحليل الحمض النووي الجنائي تحديات إجرائية وقانونية، لا سيما فيما يتعلق بشفافية خوارزميات الذكاء الاصطناعي والتحقق من صحتها. يجب على المحاكم ضمان موثوقية الأدلة القائمة على الذكاء الاصطناعي والمطالبة بتوثيق واضح لعمليات التحقق من صحة الخوارزميات وقابليتها للتكرار ومعدلات الخطأ. يركز التدقيق القانوني على معالجة القضايا المتعلقة بأنظمة "الذكاء الاصطناعي غير الشفافة"، حيث لا تكون عملية صنع القرار شفافة دائمًا، مما يثير مخاوف بشأن مقبوليتها وقابليتها للتفسير في المحكمة. بشكل عام، يمثل دمج الذكاء الاصطناعي في تحليل الحمض النووي الجنائي تقدماً كبيراً في مجال العدالة الجنائية من خلال تعزيز دقة وكفاءة التحقيقات. إن التطوير المستمر لهذه التكنولوجيا، إلى جانب وضع بروتوكولات صارمة للتحقق من صحتها واعتبارات أخلاقية، أمر بالغ الأهمية لنجاح تطبيقها في العلوم الجنائية ونظام العدالة الجنائية.
Intervention
Keywords: Artificial Intelligence (AI); Forensic DNA Analysis; Criminal Investigations; Legal Admissibility; Forensic Automation; الذكاء الاصطناعي (AI); تحليل الحمض النووي الجنائي; التحقيقات الجنائية; المقبولية القانونية; أتمتة الطب الشرعي